Kemitraan Orangtua: Memperkuat Eksistensi Karakter Islami di Era Revolusi Industri 4.0 - Nuraliah Ali; Jefry Agung Perdana (Al-Mudarris, 2020)
Moral decadence, pornography, cyberbullying, hoaxes, and hate speech are negative realities that occur in the fourth revolution industry. Parents need to take preventive steps to protect children both in the family and at school. Reconstruction of parent partnerships in schools is a necessity for children's knowledge, competitiveness, and noble character. The research with a qualitative descriptive approach aims to describe the form of partnerships between parents in schools in strengthening the existence of the Islamic personality of children in the current era of the industrial revolution 4.0. The data collection method used is a content document and data analysis techniques using content analysis techniques. The form of a partnership of parents in schools in the fourth industrial era is done by 1) reinforcement of two-way communication based on information technology, 2) Parental Classroom, 3) parents Community, 4) Parent's involvement as motivator and Inspirator, 5) parents ' engagement in Class. In the fourth industrial revolution, strengthen the existence of children's character with Islamic values can be done by following the five pillars, namely moral acting, moral knowing, moral loving, moral modelling, and compunction. Through the five pillars are expected to strengthen the existence of children's character in this disruptive era.